Surveillance Computed tomography scan- Is there a role at five years in post curative resection of colorectal cancer? - Ishani Mukhopadhyay; Dariush Kamali; Venkatesh Shanmugam (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2020)
Objectives: There are significant worldwide variations in the use of Computed Tomography (CT) scan for postoperative surveillance of patients after curative treatment for colorectal cancer.  The NICE (National Institute of Clinical Excellence) guidelines (CG131/NG151) recommends the use of 2 CT scans of chest, abdomen and pelvis in the first three years following curative resection.  Our hospital policy was to perform a third scan at five years prior to discharge from follow-up. This study aimed at determining the oncological benefit of the additional scan at 5-years post-surgery.  This current audit result will adds evidence to the planned introduction of stratified follow-up.   Method: Retrospective analysis of CT scans performed at five years post curative resection for colorectal adenocarcinoma in a single UK Trust, between December 2015 and December 2018.   Results: A total of 200 consecutive patients (133 male, 67 female; median age 73 years) were reviewed. No patients (0%) were found to have new colorectal recurrence at Year-5 scan. One patient underwent an expedited CT scan for symptoms and presence of suspicious findings on previous CT scans. The calculated sensitivity of CT scan for excluding colorectal recurrence was 100% with a specificity of 97.5%   Conclusion: The additional Year-5 CT scan beyond NICE recommended two scans did not demonstrate any significant clinical benefit in the detection of recurrence or metastatic colorectal cancer. In addition, CT scans expose patients to additional radiation risks and adds further burden to a resource-limited NHS.